Artificial Neural Network Modelling - Shanmuganathan, Subana; Samarasinghe, Sandhya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book covers theoretical aspects as well as recent innovative applications of Artificial Neural networks (ANNs) in natural, environmental, biological, social, industrial and automated systems. It presents recent results of ANNs in modelling small, large and complex systems under three categories, namely, 1) Networks, Structure Optimisation, Robustness and Stochasticity 2) Advances in Modelling Biological and Environmental Systems and 3) Advances in Modelling Social and Economic Systems. The book aims at serving undergraduates, postgraduates and researchers in ANN computational modelling. .
Artificial Neural Networks Applications: An Introduction -- Order in the Black Box: Consistency And Robustness Of Neuron Activation Of Feed Forward Neural Networks And Its Use In Efficient Optimization Of Network Structure -- Artificial Neural Networks as Models of Robustness in Development And Regeneration: Stability of Memory During Morphological Remodeling -- A Structure Optimization Algorithm of Neural Networks For Pattern Learning from Educational Data -- Stochastic Neural Networks for Modelling Random Processes from Observed Data -- Curvelet Interaction with Artificial Neural Networks -- Hybrid Wavelet Neural Network Approaches.-Quantification of Prediction Uncertainty in Artificial Neural Network Models -- Classifying Calpain Inhibitors for The Treatment of Cataracts: A Self Organising Map (SOM) ANN/KM Approach in Drug Discovery -- Improved Ultrasound Based Computer Aided Diagnosis System for Breast Cancer Using Neural Networks Incorporating a NovelEffective Feature - Degree of Central Regularity of Mass.-SOM Clustering and Modelling of Australian Railway Drivers' Sleep, Wake, Duty Profiles -- A Neural Approach to Electricity Demand Forecasting -- Development of Artificial Intelligence Based Regional Flood Estimation Techniques for Eastern Australia -- Artificial Neural Networks in Precipitation Nowcasting: An Australian Case Study -- Construction of Pmx Concentration Surfaces Using Neural Evolutionary Fuzzy Models of Semi Physical Class -- Application of Artificial Neural Network in Social Media Data Analysis: A Case of Lodging Business in Philadelphia -- Sentiment Analysis on Morphologically Rich Languages - An Artificial Neural Network (ANN) Approach -- Predicting Stock Price Movements with News Sentiment: An Artificial Neural Networks Approach -- Modelling Mode Choice of Individual In Linked Trips with Artificial Neural Networks and Fuzzy Representation -- Artificial Neural Network (ANN) Pricing Model for Natural Rubber Products Based on Climate Dependencies -- A Hybrid Artificial Neural Network (ANN) Approach to Spatial and Non-Spatial Attribute Data Mining: A Case Study Experience.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence